Chemo-radiotherapy after neoadjuvant chemotherapy and radical hysterectomy in women with stage IB-IIB cervical cancer: Do we need to change the therapeutic approach? A cohort study - Somayeh Nikfar; Azam Sadat Mousavi; Setareh Akhavan; Shahrzad Sheikhhasani; Amir Almasi-Hashiani; Ramin Parvizrad; Narges Zamani (Surgery in Practice and Science)
Background: Chemoradiotherapy is recommended as the standard treatment for advanced cervical cancer, and neoadjuvant chemotherapy (NACT) can be beneficial for patients on long radiotherapy waiting lists. This study aimed to evaluate the need for chemoradiotherapy after NACT and radical hysterectomy in women with stage IB-IIB cervical cancer. Methods: This was a retrospective, cohort study. All patients in the gynecologic oncology clinic of Imam Khomeini Hospital, Tehran, Iran, who were diagnosed with stage IB-IIB cervical cancer and treated with NACT and radical hysterectomy between 2010 and 2020, were included in this study. The records of all the patients who met the inclusion criteria were evaluated during the study period. Outcomes of interest and progression-free survival (PFS) were also assessed. Results: In this study, the clinical files of 613 patients with cervical cancer were studied, and among them, 63 patients (10.2%) underwent NACT. Eighteen patients (33.3%) did not require another treatment modality after chemotherapy and radical hysterectomy, while 66.7% (36 cases) of patients required chemoradiotherapy after NACT and radical hysterectomy, and recurrence was observed in 11.6% (5 cases) of patients. The 1-, 5- and 10-year PFS rate was 97.6% (95% CI: 84.2–99.6), 89.5% (95% CI: 74.4–95.9) and 89.5% (95% CI: 74.4–95.9), respectively. Conclusions: It can be concluded that a significant percentage of patients who are candidates for NACT followed by radical hysterectomy would require another modality of treatment, which is chemoradiotherapy; therefore, it is recommended that by conducting prospective studies, in addition to investigating this issue, the choice of the first method of patient treatment in these stages should be reconsidered so that patients do not suffer from two treatments and related complications, and undergo chemoradiotherapy from the beginning.